West of here : a novel - Evison, Jonathan (Algonquin Books of Chapel Hill, 2011)
Since the dawn of recorded history, the Klallam Indians have thrived upon the bounty of the Elwha River. In 1889, on the eve of Washington's statehood, the Olympic Peninsula remains America's last frontier. But not for long. As northwestern expansion reaches its feverish crescendo, the clock is ticking...